(untitled) (International Journal of Current Engineering and Technology, 2015)
The main purpose of our project is to create a home automation system i.e. a home which will act as an intelligent agent. Voice commands are given as an input by the user. An android application is created for this purpose. This application consists of a list of rooms, room- switches and the operations which are to be performed. We are using the current system time and weather conditions. Datasets are built for analysis purpose and then stored in the switch history table. We perform data mining on the switch history table. It means that a new record which is added in the switch history table will perform action based on the previous records which are stored. The current status is predicted and the output is sent to the Arduino kit. The corresponding led will glow for on and off state of light. A stepper motor is fixed for showing the status of the fan.